ANALISIS KOMUNIKASI DI PT. ASURANSI BUANA INDEPENDENT MEDAN - WILINNY .; CHRISSYCA HALIM; SUTARNO .; NGAJUDIN NUGROHO; FAUZI AKBAR MAULANA HUTABARAT (JURNAL ILMIAH SIMANTEK, 2019)
This research is aimed at knowing the barriers to implementing communication at PT. Asuransi Buana Independent. In theimplementation of communication also allows the emergence of obstacles. Badrudin (2013) describes these obstacles, suchas semantis barriers, technical barriers, biological barriers, psychological barriers, and ability barriers. In this research,authors use qualitative descriptive research methods. The data collection methods used are structured interviews. The datahas been collected and analyzed through three activities, namely data reduction, data presentation, and the withdrawal ofconclusions. In the withdrawal of conclusions, data credibility is checked first by using source triangulation. Conclusion ofresearch on communication barriers at PT. Asuransi Buana Independent There are four: semantis barriers, technicalbarriers, psychological barriers, and barriers of ability. In the delivery or acceptance of information, there has been amisunderstanding because of the use of words or sentences that are less precise, such as between superiors andsubordinates. The subordinates misresponded to the superiors so they misdone what he was asked to work on.Communication problems due to less good communication tools usually occur in the use of memos and messengers.Subordinates are experiencing obstacles when communicating with superiors because they have to be more cautious inspeaking and also more polite and hesitate. Not all interlocutor have a good ability to respond to messages or informationsubmitted. Error responding to messages more frequently occurs in the use of communication in writing.